2012
DOI: 10.1080/00343404.2010.521146
|View full text |Cite
|
Sign up to set email alerts
|

Rank-size City Dynamics in China and India, 1981–2004

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
14

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 41 publications
1
21
0
14
Order By: Relevance
“…The steep curve among the larger Chinese cities suggests that when it comes to big areas, China is more like Brazil than like the U.S. China also has far fewer extremely large cities than Zipf's Law would suggest. The -.91 estimate is larger in magnitude than Soo (2014), but smaller than Schaffar and Dimou (2012) and Rose (2006).…”
Section: China Indiamentioning
confidence: 66%
“…The steep curve among the larger Chinese cities suggests that when it comes to big areas, China is more like Brazil than like the U.S. China also has far fewer extremely large cities than Zipf's Law would suggest. The -.91 estimate is larger in magnitude than Soo (2014), but smaller than Schaffar and Dimou (2012) and Rose (2006).…”
Section: China Indiamentioning
confidence: 66%
“…When studying city growth in France (1876France ( -1990 and Japan (1925Japan ( -1985, Eaton and Eckstein (1997) found that the large cities maintained their ranking over the entire reference time, which means that city growth is parallel, rather than divergent or convergent. Other studies that found supports for parallel growth are Dobkins and Ioannides (2001), Black and Henderson (2003), Sharma (2003), Resende (2004), Schaffar and Dimou (2012). But another strand of lit-erature has shown that city growth presents sequential characteristics (Anderson and Ge, 2005;Henderson and Venables, 2009;Sheng and Sun, 2013).…”
Section: Introductionmentioning
confidence: 98%
“…Anderson and Ge (2005) examined the manner in which cities of different sizes grow relative to each other in China and, contrary to the common empirical finding that the relative size and rank of cities remained stable over time, it was found that the Economic Reforms and the 'One Child Policy' that has been in place since 1979 have delivered significant structural changes to the Chinese urban system (Fan, 1988). Another study by Schaffar and Dimou (2012) compared the rank-size Dynamics in China and India between 1981 and 2004. The evolution of these two distributions over the last twenty years differs.…”
Section: Introductionmentioning
confidence: 98%